Adhesives of cold curing based on chloroprene rubber brand Skaypren G-40T - Omasheva, A.V.; Sevostyanova, K.A.; Zavgorodnyaya, M.A. (KSU Publ., 2015)
New formulation of adhesives based on cold curing chloroprene rubber stamp Skaypren G-40T have been developed with a complex of adhesion, strength, performance properties that meet the requirements of modern technology. Mode of preparation of glue was installed for laboratory’s glue-stir. These adhesives have been tested for compliance with technical requirements. Formulation of adhesive was based on finding the optimal balance between the physical and mechanical properties, providing the set requirements, the technological properties which satisfy the conditions of the existing production process and economic efficiency. At the same time sought to maximize unification adhesives. For the preparation of adhesives cold rejection was used chloroprene rubber stamp Skaypren G-40T instead of the previously used Nairit chloroprene rubber stamps.
Скайпрен G-40Т маркалы хлоропренді каучукке негізделген суық қатайту желімдер
Клеи холодного отверждения, основанные на хлоропреновом каучуке марки Скайпрен G-40T
Keywords: adhesives; chloroprene rubber; glue; economic efficiency; Skaypren G-40T; physical and mechanical properties; sealing materials; Nairit rubber stamps; cold-curing adhesives